Konsep Tazkiyatun Nafs menurut Tafsir Al Misbah Karya Quraish Shihab - Hidayatullah, Syarif; Nur Fuad, Ai Fatimah (CV. Creative Tugu Pena, 2024)
This research aims to examine the concept of Tazkiyatun Nafs according to Quraish Shihab Al-Misbah's interpretation. Tazkiyatun Nafs which refers to the Islamic process of purifying the soul is the main focus of the Al-Quran which Quraish Shihab studied in his interpretation. In this research we analyze Al-Misbah's work to explore Quraish Shihab's views on this concept. The research method used includes analysis of writings related to Tazkiyatun nafs Quraish Shihab, with the aim of identifying the understanding, urgency and practical implications of this concept in the daily lives of Muslims. The results of this research are that the concept of Tazkiyatun Nafs as interpreted by M Quraish Shihab Tafsir Al-Misbah is an Islamic process of purifying the soul which is the main focus of the Al-Quran. The research method uses analysis of writings related to Tazkiyat Nafs Quraish Shihab with the aim of finding out the understanding, urgency and practical implications of this concept in the daily lives of Muslims. Keywords: Tazkiyatun Nafs, Tafsir Al Misbah, Quraish Shihab